Concentrator Improvements At Ozark Lead (MINERALS AND METALLURGICAL PROCESSING AUGUST 1984 ) - T. S. Maio; J. G. Mansanti (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
In 1978, Ozark Lead Co. made the decision to expand the capacity of its mine/mill complex by 33%. The objectives of the expansion were to increase mine production capacity by 1.8 kt/d (2000 stpd), increase lead metal production by 21.8 kt/a (24,000 stpy), and to construct new facilities and modify existing equipment to accommodate increased production. This paper gives a brief explanation of the equipment installed and the overall production and metallurgical benefits realized from this expansion. The expansion was completed in the second half of 1980 with all equipment debugging and fine tuning completed by the first quarter of 1981. Concentrator modifications and improvements were basically restricted to four areas: materials handling, automation of the mill grinding circuit, increased flotation capacity, and concentrate dewatering.